Handbook of writing research - MacArthur, Charles A.; Graham, Steve 1950-; Fitzgerald, Jill (Guilford Press, 2006)
This authoritative volume synthesizes current knowledge on writing development in children and adolescents and the processes underlying successful learning and teaching. The most comprehensive work of its kind, the volume encompasses both cognitive and sociocultural perspectives. Leading investigators present salient theoretical models; describe cutting-edge research methodologies and analytic tools; summarize available data on the effectiveness of major instructional approaches; and identify key directions for future research. Emphasizing the importance of supporting all students' writing development, the book includes a special section on cultural diversity, gender, special education, and bilingual learners.